Challenges in Teaching IELTS for Police Academy Alums at Police Language School - Firza Garuda; Zukfa Sakhiyya (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This qualitative case study examines the pedagogical challenges faced within the International English Language Testing System (IELTS) preparation program at the Police Language School (Sebasa), with a specific focus on the instruction of Police Academy graduates. Data were collected through semi-structured interviews and classroom observations involving eight instructors, comprising two representatives from each of the IELTS modules (Listening, Reading, Writing, and Speaking). The thematic analysis reveals that the primary challenge is a "motivational deficit" stemming from the clash between the students' regimented, command-based training background and the critical thinking demands of the IELTS exam. While the graduates often display passive behavior and "clique" isolation, findings indicate that Direct Instruction remains the dominant pedagogical approach as a pragmatic adaptation to the students' hierarchical culture. To mitigate disengagement, instructors utilize hybrid strategies, including gamification and English for Specific Purposes (ESP) contextualization, to bridge the relevance gap. The study concludes that effective instruction in this paramilitary context requires a pedagogical balance that respects military discipline while scaffolding the autonomy necessary for academic proficiency.